2008
DOI: 10.1158/1055-9965.epi-08-0364
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanin/Polyphenolic–Rich Fruit Juice Reduces Oxidative Cell Damage in an Intervention Study with Patients on Hemodialysis

Abstract: Hemodialysis patients face an elevated risk of cancer, arteriosclerosis, and other diseases, ascribed in part to increased oxidative stress. Red fruit juice with high anthocyanin/polyphenol content had been shown to reduce oxidative damage in healthy probands. To test its preventive potential in hemodialysis patients, 21 subjects in a pilot intervention study consumed 200 mL/day of red fruit juice (3-week run-in; 4-week juice uptake; 3-week wash-out). Weekly blood sampling was done to monitor DNA damage (comet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
2
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(49 citation statements)
references
References 51 publications
(79 reference statements)
4
37
2
2
Order By: Relevance
“…Natural antioxidants present in the grapes include anthocyanins and others flavonoids, which are ubiquitously distributed in the vegetable kingdom as secondary plant metabolites (Paganda and RiceEvans 1997). Many studies have suggested that ingesting phenolic compounds can help prevent diseases (Scalbert and Williamson 2000;Park et al 2003;Houston et al 2007;Spormann 2008;Russell et al 2009). Since grape juice has almost three times the total polyphenolic concentration of orange or grapefruit, there are large differences between the classes of juice flavonoids (Russell et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Natural antioxidants present in the grapes include anthocyanins and others flavonoids, which are ubiquitously distributed in the vegetable kingdom as secondary plant metabolites (Paganda and RiceEvans 1997). Many studies have suggested that ingesting phenolic compounds can help prevent diseases (Scalbert and Williamson 2000;Park et al 2003;Houston et al 2007;Spormann 2008;Russell et al 2009). Since grape juice has almost three times the total polyphenolic concentration of orange or grapefruit, there are large differences between the classes of juice flavonoids (Russell et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Over the last 15 years, numerous publications have demonstrated that, besides their in vitro antioxidant capacity, certain phenolic compounds, such as anthocyanins, catechins, proanthocyanidins, and other non-coloured flavonoids, may regulate different signalling pathways involved in cell survival, growth and differentiation [3]. These effects include antioxidant, antiallergic, anti-inflammatory, anti-viral, antiproliferative, anti-mutagenic, anti-microbial, anti-carcinogenic, protection from cardiovascular damage and allergy, microcirculation improvement, peripheral capillary fragility prevention, diabetes prevention, and vision improvement [4][5][6]. Compared with most fruit, berries are unusual in that they are rich in anthocyanins, which are glycosidiclinked flavonoids responsible for their red, violet, purple and blue colours.…”
Section: Introductionmentioning
confidence: 99%
“…Anthocyanins have been recognized as health-enhan cing functional food ingredients due to their antioxidative activity (Jang and Xu et al, 2009;Kamiyama et al, 2009), anticancer activity (Spormann et al, 2008;Longo et al, 2008) and prevention of arterial sclerosis (Miyazaki et al, 2008).…”
Section: Introductionmentioning
confidence: 99%